Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea - Shandikov, Gennadiy; Eakin, Richard (ZooKeys, 2013)
This paper continues descriptions of new deep-water Antarctic barbeled plunderfishes of the poorly known and the most speciose notothenioid genus Pogonophryne. It is based on a comprehensive collection obtained by the authors in 2009–2010 during an Antarctic toothfish ( Dissostichus mawsoni ) fishing trip. A new species, the hopbeard plunderfish P. neyelovi, the twenty-second species of the genus, is described. The new species belongs to dorsally-spotted short-barbeled species forming the “ P. mentella ” group. Pogonophryne neyelovi sp.n. is characterized by the following combination of characters: a very short and small mental barbel with an ovaloid and short terminal expansion covered by flattened scale-like processes that are mostly bluntly palmate; a moderately protruding lower jaw; a high second dorsal fin almost uniformly black and lacking a sharply elevated anterior lobe; pectoral fins striped anteriorly and uniformly light posteriorly; the anal and pelvic fins light; the dorsal surface of the head and the area anterior to the first dorsal fin covered with large, irregular dark brown blotches and spots; the ventral surface of the head, breast and belly without sharp dark markings. The new species is compared to the closest species P. brevibarbata , P. tronio , and P. ventrimaculata . English vernacular names are proposed for all species of the genus.